2009
DOI: 10.1111/j.1745-4573.2009.00155.x
|View full text |Cite
|
Sign up to set email alerts
|

Glycolytic Potential in Semimembranosus Muscle of Italian Large White Pigs

Abstract: The objective of this study was to determine the distribution of glycolytic potential (GP) and its relationships with meat pH and the estimated breeding values (EBVs) of some traits in Italian Large White pigs. GP was determined on samples taken from the semimembranosus muscle at 120 min postmortem. Values of GP were normally distributed around a mean value of µmol/g 103.5 ± 23.0. Increasing GP was associated with decreasing pH at 2 and 24 h postmortem. A nonlinear relationship was found between GP and pHu. GP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
2
4
0
Order By: Relevance
“…The results that characterized meat quality are in accordance with the work of Hamilton et al [30] and Nani Costa et al [31]. Resistance and reactance values reported in the study were higher compared to those observed in pigs of Yorkshire Duroc Hampshire barrows of 109.4 kg [32], Yorkshire Duroc pigs of 103 kg [33], and 109.2 kg Iberian pigs of Torbiscal line [34].…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The results that characterized meat quality are in accordance with the work of Hamilton et al [30] and Nani Costa et al [31]. Resistance and reactance values reported in the study were higher compared to those observed in pigs of Yorkshire Duroc Hampshire barrows of 109.4 kg [32], Yorkshire Duroc pigs of 103 kg [33], and 109.2 kg Iberian pigs of Torbiscal line [34].…”
Section: Resultssupporting
confidence: 91%
“…The meat of fatteners from cluster 2 was characterized by lower ultimate pH, higher GP, and color b* value, while the meat from cluster 3 was intermediate between both previous in meat quality traits (pH 24 , GP, and color b* value) and completely different from both in terms of resistance (R z ). Regarding the meat quality traits, the obtained relationship between the characteristics with regard to pH, GP, and color were consistent with the results of the studies by Hamilton et al [30], Nani-Costa et al [31], and Copenhafer et al [43]. Cluster analysis showed that bioimpedance measurements combined with meat quality traits make it possible to distinguish groups with different quality parameters.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…For glycolytic potential (GP) determination, samples of the same muscle were collected at 30 min postmortem and immediately frozen in liquid nitrogen and later freeze-dried. This variable was measured according to Monin et al (1987) and Nanni Costa et al (2008) separately determining lactate content and the sum of glycogen, glucose, and glucose-6-phosphate. Briefly, lactate content was measured using the l-Lactic acid BioAnalysis kit (Boehringer Mannheim/R-Biopharma, R-Biopharma GmbH, Darmstadt, Germany).…”
Section: Performance Test Carcass and Meat Quality Traitsmentioning
confidence: 99%
“…The major component of GP and the prevalent storage form of carbohydrate in skeletal muscle is glycogen, whose content and breakdown play a major role in the biochemical changes occurring postmortem in the muscle tissue. Changes in the GP of a muscle affect the pH decline: after slaughtering, the oxygen level decreases and, to satisfy the energy demand of the cells, muscle glycogen is mobilized towards the formation of glucose and lactate via glycogenolysis and anaerobic glycolysis pathway (Nanni Costa et al, 2009). As anaerobic glycolysis is undeniably the dominant pathway postmortem, muscles with high GP levels usually show a lower ultimate pH 3 that, in turn, affects other quality traits such as meat color, water holding capacity (WHC), drip loss, tenderness, and processing yield (Enfält, Lundström, Hansson, Johansen, & Nyström, 1997;Nanni Costa et al, 2009).…”
Section: Introductionmentioning
confidence: 99%